1988
DOI: 10.1038/331180a0
|View full text |Cite
|
Sign up to set email alerts
|

The mast cell binding site on human immunoglobulin E

Abstract: Antibodies of the immunoglobulin E isotype sensitize mast cells and basophils for antigen-induced mediator release by binding through the Fc portion to a high-affinity receptor (Fc epsilon R1, Ka = 10(9)M-1) on the cell surface causing the clinical manifestations of type I hypersensitivity. As the amino acid sequence of the human epsilon chain is now known, attempts have been made to map the Fc epsilon R1 binding site on IgE to a fragment smaller than Fc epsilon using proteolytic cleavage products, none of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
3

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(100 citation statements)
references
References 20 publications
4
93
3
Order By: Relevance
“…Fc⑀3-4 lacks the C⑀2 domains of the complete IgE Fc, but we have shown previously that not only does this fragment display a 1:1 stoichiometry of binding (9), it also retains full binding affinity (10), although the kinetics of binding are affected (3). It has been reported previously that deglycosylation of IgE has little effect upon receptor binding (11) and that E. coli expressed fragments retain high-affinity receptor binding activity (12). This is in contrast to the behavior of IgG where the loss of carbohydrate from the Fc destroys receptor binding altogether (13).…”
Section: Immunoglobulin E (Ige)contrasting
confidence: 48%
“…Fc⑀3-4 lacks the C⑀2 domains of the complete IgE Fc, but we have shown previously that not only does this fragment display a 1:1 stoichiometry of binding (9), it also retains full binding affinity (10), although the kinetics of binding are affected (3). It has been reported previously that deglycosylation of IgE has little effect upon receptor binding (11) and that E. coli expressed fragments retain high-affinity receptor binding activity (12). This is in contrast to the behavior of IgG where the loss of carbohydrate from the Fc destroys receptor binding altogether (13).…”
Section: Immunoglobulin E (Ige)contrasting
confidence: 48%
“…On the other hand, Helm et al recently suggested that the FcERI-binding site on human IgE was located within the sequence Gln30'-Arg376 in the junction between the CH2 and CH3 domains [12,20]. Therefore, we continued the synthesis of the peptide fragments within the sequence Ser3m-Lys547 of the human IgE molecule to determine the exact site responsible for the IgE-FceRI 226 interaction.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the synthetic human IgE peptide fragments were tested for inhibitory activity of passive sensitization of human peripheral basophils with atopic patient's serum (allergen specific human IgE) in vitro. On the other hand, it has recently been suggested that the FceRI-binding site on human IgE is located within the sequence Gln30'-Arg376 in the junction between the CH2 and CH3 domains [12]. To pinpoint the binding site more precisely, we continued the synthesis of peptide fragments within the sequence Ser300-Lys547 corresponding to the C-terminus in the human IgE molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Sites within the Cε2, Cε3, and Cε4 domains of human IgE were selected for synthesis as peptide immunogens based on previous observations and structural models that suggested potential effector sites [5,8,14]. These sites were also analyzed for surface-exposed loop structures deduced from models for the three-dimensional structure of IgE-FcεRI [8,16,33].…”
Section: Identification Of the Ige Target Sitementioning
confidence: 99%
“…The site on human IgE responsible for binding to FcεRI has been associated with the Cε2, Cε3, and Cε4 domains by binding inhibition studies involving recombinant IgE truncations [5,6], chimaeric IgE [7], site-directed mutagenized IgE [8,9], synthetic peptides corresponding to IgE Fc domains and antibodies induced by such peptides [10][11][12][13][14], and mimetope peptides [9,15]. These observations pointed to a highly conformational receptor binding site that has recently been solved by resolution of the crystal structure of a human IgE-FcεRI complex.…”
Section: Introductionmentioning
confidence: 99%